Language Change and Social Context in Mass and Social Media - Rini Afrilesa J; Helmita Helmita (Fakultas Sastra Universitas Ekasakti, 2022)
Wardhaugh in Chaer and Agustina distinguishes two types of language change: internal and external change. Internal changes occur from within the language itself, such as phonological, morphological, or syntactic changes. External changes occur due to outside influences, such as borrowing or absorption of vocabulary, the addition of phonemes from other languages and so on. The purpose of this research is (1) to analyse the language change that can be found in mass media and social media. (2) to analyse the social context that can be found in mass media and social media. The method used in this research is the qualitative method. The data was taken from Padang Express newspaper and Facebook. From the analysis there are so many languages change that can be found in mass and social media. Many people change the language when they used it in mass and social media.